ACCOUNTING FOR RESEARCH AND DEVELOPMENT COSTS AND SIMILAR COSTS: DIFFERENCES AND SIMILARITIES BETWEEN US GAAP, IFRS AND GERMAN COMMERCIAL CODE - Schreiber, Susanne (Journal of European Economy, 2017)
Owing to their very nature which makes evidence elusive, accounting for intangibles involves many problems. Within the context of US GAAP, there are many standards providing guidance in the financial reporting treatment of specifically identifiable intangibles, for instance standards on accounting for research and development costs, computer software costs, advertising costs, and costs of start-up activities. In this paper, all these standards are analyzed and compared with the relevant financial reporting treatment according to IFRS and German Commercial Code.Regardless of the different financial reporting goals of US GAAP and IFRS on the one hand and German Commercial Code on the other, this paper reveals that accounting for R&D costs and similar costs is always dominated by conservatism. This result can be explained with the agency theory. Moreover, in comparison with IAS/IFRS and German Commercial Code, US standards on accounting for these intangibles implicitly offer more alternative accounting treatments.